Case Report: Cardiac Rehabilitation in a Patient with MVR & AVR & Tricuspid Valve Repair - Babak Gousheh; Shahrbanou Ra'eiyat; Mehri Haj-Mirzaei; Fatemeh Nasseri (University of Social Welfare and Rehabilitation Sciences, 2003)
Patient is a 24 year .old male with valvular heart disease, severe mitral & aortic & tricuspid valve stenosis and regurgitation. After MVR & AVR & tricuspid surgical repair, he has undergone cardiac rehabilitation for 8 weeks (24 sittings). After completion of a cardiac rehabilitation, review of cardiovascular tests showed obvious improvement in the functional capacity, blood pressure and heart rate. Physically and mentally patient feels very comfortable and hopeful of a good healthy life.